Impact of contacting geometries on measured fill factors. (September 2017) - Kruse, Christian N.; Wolf, Martin; Schinke, Carsten; Hinken, David; Brendel, Rolf; Bothe, Karsten
Abstract: The fill factor determined from a measured current-voltage characteristic of a bare solar cell depends on the number and positions of the electrical contacting probes. Nine different geometries for contacting the front side busbars are used to measure the current-voltage (I-V) characteristics of a 5 busbar industrial-type passivated emitter and rear totally diffused (PERT) solar cell under standard testing conditions. The fill factors of the measured I-V characteristics vary from 78.5 %abs to 80.6 %abs . We further measure the contacting resistance of 3 different contacting probes to estimate the sensitivity of measurements with different contacting geometries on random resistance variations. The contacting resistance is 60 mΩ for nine-point probes and 80 mΩ for four- and single-point probes. We determine the magnitude of contacting resistance variations from measurements at different probe positions to be ±30 mΩ. Using this variation, we perform numerical simulations and find a larger sensitivity on random resistance variations for tandem- (pairs of current- and sense probes) compared to triplet (one sense- between two current probes) configurations. The corresponding fill factor deviation is approximately 0.1%abs for tandem configurations when the contacting resistances of up to two current probes are altered. The sensitivity for triplet configurations is negligible.